Manajemen Event Budaya Sebagai Daya Tarik Wisata di Kabupaten Ponorogo - Anggoro, Ayub Dwi; Susanto, Happy; Arifin, Rizal; Nugroho, Oki Cahyo; Purwati, Eli; Ridho, Irvan Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This study aims to determine the strategy of the Ponorogo district government in carrying out various efforts to promote or compare Ponorogo culture as a tourist attraction strategy. Therefore to organize an event, event management is needed. This research method uses the library research method, namely research that collects information and data with the help of various materials available on the internet and libraries, such as reference books, previous similar research results, articles, notes, and various journals. The results of this study discuss cultural events that have been held by the Ponorogo district government. In making a cultural event, the organizer also goes through several stages of event management as proposed by Goldblett (2002), namely from the research, design, planning, coordination, and evaluation stages.